Penggunaan Metode Jigsaw Berbantuan Modul Mengefektifkan Prestasi Belajar Peserat Didik Dalam Pendidikan Agama Katolik Di Kelas II SD Kanisius Tlogosari Kulon (International Forum of Researchers and Lecturers, 2023)
Low learning results as a result of the school system's inefficiency and slowness. It seems like grade II students at SD Kanisius Tlogosari Kulon still have a low feeling of responsibility. Many of them are still tardy to class and afraid to ask questions, which causes them to not understand the lessons that are being taught. The purpose of this study is to evaluate the impact of the jigsaw technique and module-assisted learning on students' learning outcomes for PAK learning. Experimental quantitative research is the name for this kind of study. One group pretest and posttest study design is employed. Tests and questionnaires are used as data collection strategies. In this study, descriptive statistical analysis was used for data analysis. 91.77 is the average score for student responsibility, according to data analysis. The average pre-test score was 59.23, and the average post-test score was 88.85. The N-Gain Test classifies the coefficient of determination R2 at 0.783 = 78.3% as high. Using an independent sample t test, test your hypotheses. In the statistical analysis of the responsibility questionnaire, the Sig. (2-tailed) = 0.000 = 0% <0.05%. From these data, it can be concluded that the use of the jigsaw method assisted by modules is considered effective in learning Catholic Religious Education (PAK) in class II of Kanisius Tlogosari Elementary School.